2021
DOI: 10.3390/ma14195531
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Wear and Material Integrity of NAO and Low-Steel Brake Pads under Severe Conditions

Abstract: In this study, through severe reduced-scale braking tests, we investigate the wear and integrity of organic matrix brake pads against gray cast iron (GCI) discs. Two prototype pad materials are designed with the aim of representing a typical non-metal NAO and a low-steel (LS) formulation. The worn surfaces are observed with SEM. The toughness of the pad materials is tested at the raw state and after a heat treatment. During braking, the LS-GCI disc configuration produces heavy wear. The friction parts both kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…However, when using NAO brake pads, the increase in pad wear at high mechanical and thermal loads must also be taken into account. In some cases, this has also been reflected in the emission of particulate matter [12,27]; however, in the current study we did not notice such a trend. In particular, it has been reported that (volatile) ultrafine dust is generated by 'outgassing' of the organic lining matrix [11].…”
Section: Influence Of the Brake Pad/shoe Compositioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, when using NAO brake pads, the increase in pad wear at high mechanical and thermal loads must also be taken into account. In some cases, this has also been reflected in the emission of particulate matter [12,27]; however, in the current study we did not notice such a trend. In particular, it has been reported that (volatile) ultrafine dust is generated by 'outgassing' of the organic lining matrix [11].…”
Section: Influence Of the Brake Pad/shoe Compositioncontrasting
confidence: 74%
“…Since this is the standard friction pairing for the European market, it serves as a benchmark in the following analysis and discussion. At this point, high demands in Europe on the braking performance and temperature stability of the friction systems, especially on German motorways, require somewhat aggressive brake pads, which at the same time lead to correspondingly high wear [27]. In particular, it is the wear of the brake disc that comes to the foreground due to the abrasive effect of the ECE brake pads (cf., Figure 5).…”
Section: Brake Pad Compositionmentioning
confidence: 99%
“…Low-steel type brake pads tend to cause more brake emissions than nonsteel pads because of their high level of aggressiveness toward the corresponding gray iron discs. In addition, brake discs with lower surface hardness have higher brake emissions due to higher disc wear [6,[21][22][23][24][25][26][27][28][29]. On the other hand, there have been reports comparing non-steel and steel pads, where pad and disc wear factors are comparable, but brake emissions are lower for non-steel pads [26,27], so the effect of pad and disc wear factors on brake emissions is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Its use has been forbidden due to its carcinogenic properties [ 5 ]. In brake pads, it worked perfectly as reinforcement [ 6 , 7 ]. It is a fiber of natural origin, so its production did not cause unnecessary contamination.…”
Section: Introductionmentioning
confidence: 99%